Analisis Dampak UU TNI 2025 Terhadap Potensi Terbentuknya Junta Militer - Nuzulianto, Fiqri Maulana; Sukalumba, Ilham Saputra (Penerbit Goodwood, 2025)
Purpose: The purpose of this scientific article is to analyze the expansion of the position and role of the TNI in the 2025 TNI Law regarding the potential formation of a Military Junta in the Unitary State of the Republic of Indonesia, as well as to compare the involvement of the Military in the political realm that occurs in Indonesia and Myanmar. Methodology/approach: The article was prepared using a qualitative method with a case study approach. Data collection was performed using library study and triangulation data analysis techniques. Results/findings: Results show that Myanmar's military dominance stems from authoritarian history and constitutional shifts. In contrast, Indonesia's 2025 TNI Bill expands military roles within state operations but raises concerns over democratic decline due to its non-transparent legislative process. Conclutions: The expansion of the position and role of the TNI based on the TNI Bill 2025 does not have the potential to create a Military Junta, but there needs to be supervision of every policy issued by the government related to the role and function of the TNI. Limitations: This paper is limited to the impact of the expansion of military positions in the TNI Law, which has the potential to create a military junta. In addition, the approach used in the analysis was limited to case studies and legislation. Contribution: This research contributes to the social, political, and legal fields that discuss the revision of the TNI Law, which has received various responses from local and global communities.